ANALISIS METHOD DALAM DEBAT “KENAKALAN ANAK SD” PADA PEMBELAJARAN KETERAMPILAN BERBAHASA - Anita Dewi Kurniasari; Atiqa Sabardila (Linguistik : Jurnal Bahasa dan Sastra, 2020)
his article attempts to analyze the graduate student debate method in encouraging skills learning. The subject was a second year MPBI students at the Muhammadiyah University of Surakarta. Focuses on Analysis Methods of postgraduate student debates in learning skills. Data translated from the sentence transcript of the debate "Delinquency of Elementary Children". The technique of collecting data uses the recording technique and the note taking technique. The method used is descriptive qualitative, namely research by describing transcription using descriptive data analysis. The results showed five aspects; 1) Moderators are able to be good opening arguments to start the discussion process. 2) The delivered criticism is able to show good thinking skills and also measurable. 3) Ideas that are conveyed by understanding the topics that can be conveyed clearly. 4) Priority scale can be seen through the discussion of the conveyance which is clearly and structured. 5) Time allocation is less than 30 minutes. In general, the closing remarks on the elementary school delinquency debate have not shown a solution.